Implementation Of Principal Leadership At SMP N 2 Tombatu - Jelly Maria Lembong; Paulus Robert Tuerah; Viktory N.J. Rotty (International Journal Labs, 2024)
The most effective effort to improve human quality is through education. Education functions as a transmission of knowledge, skill values, and culture. In education, the aspects of rationality, dignity, ethics, and aesthetics are highly emphasized because in the long run, the current students are the leaders and actors of Indonesia's future culture. The purpose of this study is to analyze and describe the implementation of principal leadership at SMPN 2 Tombatu. This research method uses a qualitative method. In this study, the implementation of principal leadership at SMP N 2 Tombatu is evaluated through a triangulation approach, namely through the perspective of the principal, teachers, and parents of students. The conclusion of this study shows that the implementation of principal leadership at SMP N 2 Tombatu has a holistic approach and is oriented towards improving the quality of education. The principal, through a clear vision and professional development of the staff, manages to create a conducive and supportive learning environment for students. From the teacher's perspective, the principal's leadership is considered effective in providing the necessary direction and support to achieve the school's goals, as well as implementing open and transparent communication.